A history of English literature - Alexander, Michael (Palgrave MacMillan, 2000)
This book provides a comprehensive survey of English literatures. Presented as a narrative, and usable as a work of reference, this text offers an account of literature from the beginnings of English until the present day. The author begins by examining the scope of such a history in terms of time, place, and the meaning of "English". The classical status of any particular work is open to challenge, and the notion of classical status itself is explored. The text is unrivalled in its use of pedagogical features and exhibits, offering invaluable insights into particular works, authors' biographies, and literary periods (Back cover)